Analisis Penguatan Konsep Rehabilitasi dengan Metode Therapeutic Community (TC) Terhadap Narapidana Narkoba untuk Kepastian Hukum - Diva Larasti; Togar Natigor Siregar; Endeh Suhartini (Universitas Proklamasi 45, 2025)
This study aims to analyze the implementation and effectiveness of the Therapeutic Community (TC) method as a rehabilitative approach for prisoners convicted of drug abuse at the Bogor Class IIA Correctional Institution. Using a legal-normative approach based on a literature review and legal regulations, it was found that the implementation of the TC method in practice still faces various challenges, including a shortage of professional staff, inadequate supporting facilities, and limited active participation by inmates. These obstacles result in a mismatch between legal norms and institutional practices, which undermines the weak legal certainty needed to fulfill rehabilitation rights. Therefore, policy reformulation, institutional capacity building, and cross-sectoral collaboration are necessary to achieve effective and sustainable rehabilitation in support of the social reintegration of inmates.